Adverbial Ekstraklausal Bermakna ‘Pelimitan’ dalam Bahasa Indonesia - Novia Juita (Fakultas Bahasa dan Seni UNP, 2011)
The meaning of the extra-clause adverbs in this paper constitutes the functional elements of sentences that are peripherals and are outside the clause structure. Some experts call this type of adverbs disjunct, stance adverbs and sentence adverbs. The existence of this type of adverbs is specifically to provide information or additional explanation regarding the establishment, point of view or comment on the proposition contained in a sentence. This paper only discusses one type of extra-clause adverbs, i.e. the one that functions as the restrictions. Keywords: extra-clause adverbs, restriction, Indonesian Language